Respuesta :

Answer:

[tex]-3x^2 * x = -3x^3\\y * y = y^2[/tex]

[tex](-3x^2y)(5xy^2 + xy)\\[/tex]

Use F.O.I.L, (First Outer Inner Last) to multiply. Start with -3x^y * 5xy^2

Start with similar terms

[tex]-3x^2 * 5x = -15x^3\\y * y^2 = y^3\\Therefore,\\-15x^3y^2[/tex]

Move onto the xy portion of the problem

[tex]-3x^2y(xy)\\[/tex]

Start with similar terms

[tex]-3x^2 * x = -3x^3\\y * y = y^2\\Therefore,\\-3x^3y^2[/tex]

Combine the two together

[tex]-15x^3y^3 - 3x^3y^2\\[/tex]

The answer is Option A

Answer:

   44. (1) -15x³y³ - 3x³y²

Step-by-step explanation:

Question 44

  • -3x²y (5xy² + xy)
  • (1) -15x³y³ - 3x³y²